Participatory Learning and Action (PLA) as an Intervention to Reduce Iron Deficiency Among Pregnant Women: First-Year Findings from a Study in West Lombok - Erien Luthfia; Lina Sundayani; Hadi Kusuma Atmaja (Postgraduate, University of Mataram, 2026)
Anemia during pregnancy remains a significant public health problem, particularly in Indonesia where prevalence exceeds the global average. This study evaluated the effectiveness of a Participatory Learning and Action (PLA) intervention in improving knowledge of iron-deficiency anemia among pregnant women in West Lombok. A quasi-experimental pre–posttest design was conducted with 60 pregnant women divided into intervention and control groups. The intervention involved six PLA sessions focusing on community discussions, nutrition education, and family participation. Knowledge scores were analyzed using paired t-tests and Mann–Whitney U tests, complemented by effect sizes and qualitative thematic analysis. Results showed a substantial improvement in the intervention group, with the proportion of good knowledge increasing from 20.0% to 80.0% and mean scores rising from 11.5 ± 2.5 to 16.8 ± 1.8 (p < 0.001). The control group showed no significant change. Qualitative findings revealed improved spousal support, effective reminder strategies, and increased motivation among health cadres. PLA is an effective and scalable community-based approach for strengthening anemia prevention in maternal health programs.